Therapeutic potential of glial cell line-derived neurotrophic factor and cell reprogramming for hippocampal-related neurological disorders - Chiavellini, Priscila (2021)
Hippocampus serves as a pivotal role in cognitive and emotional processes, as well as in the regulation of the hypothalamus-pituitary axis. It is known to undergo mild neurodegenerative changes during normal aging and severe atrophy in Alzheimer’s disease. Furthermore, dysregulation in the hippocampal function leads to epilepsy and mood disorders. In the first section, we summarized the most salient knowledge on the role of glial cell-line-derived neurotrophic factor and its receptors focused on aging, cognition and neurodegenerative and hippocampal-related neurological diseases mentioned above. In the second section, we reviewed the therapeutic approaches, particularly gene therapy, using glial cell-line-derived neurotrophic factor or its gene, as a key molecule in the development of neurological disorders. In the third section, we pointed at the potential of regenerative medicine, as an emerging and less explored strategy for the treatment of hippocampal disorders. We briefly reviewed the use of partial reprogramming to restore brain functions, non-neuronal cell reprogramming to generate neural stem cells, and neural progenitor cells as source-specific neuronal types to be implanted in animal models of specific neurodegenerative disorders.